Marrying Winterborne [large type] - Kleypas, Lisa (Kleypas, Lisa. Ravenels., 2016)
Achieving wealth and success through his savage ambitions, tycoon Rhys Winterborne resolves to marry shy, aristocratic Lady Helen Ravenel. In spite of her gentle upbringing, she responds to Rhys' seductions with her own unexpected passions.